SEDIMENTOLOGI BATUGAMPING FORMASI JONGGRANGAN DI SEPANJANG LINTASAN GUA KISKENDO, GIRIMULYO, KULONPROGO - Sigit Maryanto (Pusat Survei Geologi, 2013)
The Early Miocene limstone of the Jonggrangan Formation is cropped out at Gua Kiskendo Section, Kulonprogo Regency. Detailed stratigraphic sections were measured out along twelve kilometers section to predict the development of their depositional environments. Limestone petrography analysis are useful to sharpening the limestone microfacies interpretations. Based on petrography data from thirty eight samples, this limestone formation composes of boundstone, floatstone, grainstone, packstone, wackestone, mudstone, and crystalline limestone. The depositional environments of this formation are regressive condition, include fore-reef facies, organic reef facies, reef flank facies, shelf lagoon with open circulation facies, and shallow marine until local basin on back reef with open circulation facies.Keywords: Miocene, petrography, sedimentology, limestone, reef.